Nursing management of drug-induced dermatitis in a patient with oral administration of ibuprofen suspension (1例口服布洛芬悬液致药物性皮炎患者的护理体会) - YAO Xiaohan (姚晓晗); PENG Ya (彭娅); ZHU Lifang (朱莉芳) (中西医结合护理)
This paper summarized the nursing management of drug-induced dermatitis in a patient with oral administration of ibuprofen suspension. Key issues including conjunctiva care, oral hygiene, skin care, nutrition, mental status, health education about disease and medication should be considered. After implementation of symptomatic treatment and individualized nursing, the patient had completed the following neoadjuvant chemoradiotherapy. (总结1例口服布洛芬悬液致药物性皮炎患者的护理经验, 包括结膜护理、口腔护理、皮肤护理、营养护理、心理护理、疾病知识宣教和用药指导, 通过实施对症治疗以及个体化护理方案, 患者好转, 继续行辅助放化疗后出院。)